Differential expression of for, fax, and U2Af orthologs among three termite castes of the termite, Reticulitermes flavipes (Isoptera: rhinotermitidae) - Urban, Joshua Raymond (Kansas State University, 2010)
Termites (Isoptera) are eusocial insects and exhibit highly complex eusocial behavior. Eusociality is characterized by the presence of castes (workers, soldiers, reproductives), polyphenisms (same genotype exhibiting multiple phenotypes), flexible developmental pathways, complex communication, cooperative brood care, construction and maintenance of complex nests, and division of labor. Previous studies on honey bees implicated several genes in caste-specific behavior; here, we investigate if orthologs of such genes are present in termites and if so, whether they are expressed differentially among the castes. A candidate gene approach using degenerate primers was used to amplify three candidate genes in the termite Reticulitermes flavipes. Quantitative real time PCR analysis revealed differential expression among termite workers, soldiers, and alates, with a general pattern of higher expression in alates. These results provide information on three novel genes in the termite R. flavipes.
Keywords: Reticulitermes flavipes; Termite; Differential gene expression; Social behavior; Quantitative polymerase chain reaction; Biology, Entomology (0353); Biology, Genetics (0369); Biology, Molecular (0307)